2012
DOI: 10.3892/mmr.2012.1202
|View full text |Cite
|
Sign up to set email alerts
|

FHL1 and Smad4 synergistically inhibit vascular endothelial growth factor expression

Abstract: Vascular endothelial growth factor (VEGF) plays an important role in many disease states, including ischemia, chronic and acute inflammation, and pathologies associated with angiogenesis such as tumors and wounds. A number of factors regulate VEGF promoter activity and VEGF expression such as four and a half LIM domains 1 (FHL1) and Smad4. FHL1 belongs to a family of LIM-only proteins that regulate gene transcription, cell proliferation, differentiation and apoptosis. Smad4 is a tumor suppressor gene, initiall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Finally, MS revealed that hypoxia altered the ubiquitination of Four and a half LIM domain 1 (Fhl1). Fhl1 is involved in muscle development 57 and plays an important role in gene transcription and cell proliferation, differentiation, apoptosis and cytoskeletal remodeling 58 . There is previous evidence that Fhl1 is important in vascular remodeling in PH, 57 though we were unable to find any reports of Fhl1 ubiquitination.…”
Section: Resultsmentioning
confidence: 67%
See 1 more Smart Citation
“…Finally, MS revealed that hypoxia altered the ubiquitination of Four and a half LIM domain 1 (Fhl1). Fhl1 is involved in muscle development 57 and plays an important role in gene transcription and cell proliferation, differentiation, apoptosis and cytoskeletal remodeling 58 . There is previous evidence that Fhl1 is important in vascular remodeling in PH, 57 though we were unable to find any reports of Fhl1 ubiquitination.…”
Section: Resultsmentioning
confidence: 67%
“…Fhl1 is involved in muscle development 57 and plays an important role in gene transcription and cell proliferation, differentiation, apoptosis and cytoskeletal remodeling. 58 There is previous evidence that Fhl1 is important in vascular remodeling in PH, 57 though we were unable to find any reports of Fhl1 ubiquitination. We observed increased ubiquitination of Fhl1 at K295 (3.1 FC H/N) and decreased ubiquitination at K173 (2.1 FC N/H).…”
Section: Validation Of Selected Proteins By Western Blottingmentioning
confidence: 58%
“…Studies have shown that many growth factors and their receptors play roles in tumor invasion and metastasis (Bachelder et al, ), including the VEGF system, and the regulation of this signaling axis has become a major focus of current research. A previous study (Zhou et al, ) showed that a reduction in Smad4 abrogated FHL1‐mediated inhibition of the VEGF promoter activity in HepG2 cells. Overexpression of FHL1 and Smad4 synergistically inhibited the secretion of VEGF, and knockdown of Smad4 and FHL1 had opposite effects.…”
Section: Discussionmentioning
confidence: 94%
“…The Hhub FHL1 encodes a four-and-a-half-LIM-domain protein involved in gene transcription regulation, cytoarchitecture, cell proliferation, and signal transduction [68]. Interestingly, FHL1 inhibits the vascular endothelial growth factor (VEGF) expression [69] and elevated serum levels of VEGF were positively correlated with disease severity in COVID-19 [70]. The Hhub MISP3 codes for a protein involved in spindle orientation and mitotic progression [71].…”
Section: Black Modulementioning
confidence: 99%